Comparison between the open and minimally invasive repair technique in acute Achilles tendon injuries - Primo de Araujo, João Paulo; Mota Garcia Moreno, Marcus Vinicius; de Souza Guimarães, Janice; Torres Gomes, Marilton Jorge; Marçal Vieira, Túlio Eduardo; Souza Jalil, Vitor (Scientific Journal of the Foot & Ankle, 2018)
Objective: To compare the functional results of patients submitted to open repair of the Achilles tendon in relation to those treated with the minimally invasive technique using PARS, with a minimum period of 1 year, as well as the complication index of the two techniques. Methods: Between 2011 and 2016, 31 patients were reviewed, including 20 cases (10 PARS X 10 Open technique). Patients with chronic Achilles tendon rupture, insertional or bilaterial, patients with a history of surgery or previous ankle pathology that could mask the functional results were excluded. The open technique was performed through a posteromedial incision to the ankle, repairing the tendon associated with the myotendinous transfer of the flexor hallucis longus, which was fixed with a biotenodetic screw. The minimally invasive technique was performed with the PARS (percutaneous Achilles repair system) of the company Arthrex, through a small transverse incision on the site of rupture of the Achilles tendon. Functional outcomes and complications were collected after at least 1 year of follow-up. Results: Both groups presented similar AOFAS scores (PARS: 95.3 ± 5.1, Open: 96.5 ± 5.1, P=0.604), showing similar functional results. Regarding the complications, the PARS obtained a greater number of complications in relation to the Open technique (PARS: 20% X Open: 10%), but without statistical relevance (P=0.383). Conclusion: We conclude that for the treatment of acute Achilles tendon injuries, the PARS and Aberta techniques have similar functional results after 1 year of follow-up. Level of Evidence IV; Therapeutic Studies; Cases Series.